The Sound of Music [videorecording] - Chaplin, Saul.; Wise, Robert; Argyle Enterprises, Inc.; Twentieth Century Fox Production ([S.l.] Twentieth Century Fox, 1965)
A musical film based on the true-life story of the Trapp family of Austria prior to World War II.
Based on the book by Howard Lindsay and Russell.
Originally produced on stage by Leland Hayward, Richard Halaliday, Richard Rodgers and Oscar Hammerstein II.
VHS.
Credits : Music by Richard Rodgers, Lyrics by Oscar Hammerstein II.
Julie Andrews, Christopher Plummer, Richard Haydn, Peggy Wood, Eleanor Parker as the Baroness.
1965 Academy Award Winner.
Keywords: Trapp family; Feature films; Musical films